THE DEADLINE FOR AN APPEAL AFTER THE COMPLETION OF A FULL COURT DECISION IN CASES THAT ARE URGENT - Panova, Iryna (The Journal of V. N. Karazin Kharkiv National University. Series Law, 2025)
Introduction. This article discloses problematic issues related to the terms of appeal of court decisions after drafting a full court decision in cases that are urgent in administrative proceedings. The review process determines the state of stability of the legal system and the fairness of court decisions. The article reveals the factors that influence the efficiency and duration of appeal administrative proceedings, the improvement of such a procedure, and the factors that can influence the speed and increase the efficiency of consideration of administrative cases, which, in turn, also has a decisive influence on the level of trust of citizens in the administrative process. Appellate administrative proceedings are the stage of judicial review of cases in Ukraine, at which the decision of the administrative court of first instance is reviewed.Summary of the main results of the study. According to the analyzed domestic sources that regulate the legal application of the provisions of administrative proceedings in Ukraine, including taking into account the fruits of the doctrinal developments of scientists, which reveal the aspects of appellate administrative proceedings in this court, several significant factors can be singled out, which have a decisive influence on the efficiency of appeal administrative proceedings. These include the vagueness of the procedure for calculating the time limit for an appeal, the problem of inadequate legal and regulatory support for procedural requirements in preparation for consideration of an administrative case in an appellate court. Also, the court of the first instance may not take into account the negative instructions of the appellate administrative court when sending the case for further consideration by the appellate court. Another problem in administrative proceedings is the improper observance of established statutory deadlines for consideration of appeals, which may lead to the impossibility of implementing the principle of discretion by the administrative appeals court.Conclusion. This article proposes to solve problematic issues and fill gaps in national legislation in order to determine the procedure for calculating time limits in the case of administrative appeals of court decisions of first instance courts in cases that are urgent.